The Effect Of Giving Lemon Aromatherapy And Health Education On Pregnancy Anxienty Covid 19 Pandemic At Dungingi Health Center And Kota Barat Health Center The City Of Gorontalo - Juli Gladis Claudia; Puspita Sukmawaty Rasyid (Institute of Computer Science (IOCS), 2021)
Psychologically, mothers experience anxiety during pregnancy because they are worried that the baby will be born healthy or not, especially during Covid-19 pandemic. Pregnant women who are not prepared enough for giving birth will be more anxious and show fear and behave in silence or crying, if this continues until labor can cause pathological condition (Wa Ode et al, 2013). This study aimed to identify the effect of anxiety in pregnancy before and after being given lemon aromatherapy and health education. This research was a quasi-experimental using one-group pre-test post-test control design with cases of anxious third trimester pregnant women who are given lemon Aromatherapy and cases control of anxious third trimester pregnant women who was given education through books at the same time. The research was carried out in the working area of ​​Kota Barat Public Health Community and Dungingi Public Health Community in Gorontalo City from August to November 2020. The provision of lemon aromatherapy and health education as independent variable, the anxiety level of the third trimester of pregnant women as dependent variable. The research subjects were carried out by selecting samples that met the inclusion criteria, totaling 60 pregnant women in the third trimester and divided into the intervention group and the control group. Data analysis using Paired T-test with free sample test and difference test. The results of the study of the two groups, the mean value of the intervention group had a higher difference in anxiety level score reduction (9.6) than the control group (4.0) with significance value of 0.000 and 0.038, respectively (α = 0.05). The conclusion was, there is an effect of lemon aromatherapy and health education on the anxiety level of pregnant women in the third trimester of the Covid 19 pandemic at the Dungingi Health Center and the West City Health Center, Gorontalo City.